2019
DOI: 10.3892/mmr.2019.10251
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑30a‑5p promotes proliferation and inhibits apoptosis of human pulmonary artery endothelial cells under hypoxia by targeting YKL‑40

Abstract: Pulmonary arterial hypertension (PAH) is a fatal and currently incurable cardiopulmonary disease. Numerous microRNAs (miRNAs) serve important roles in the development of PAH. While the expression of miR-30a-5p was downregulated in the lung tissue of rats in a pulmonary hypertension rat model, the expression pattern and function of miR-30a-5p in human PAH remain unclear. Reverse transcription quantitative polymerase chain reaction (RT-qPCR) was used to examine miR-30a-5p and chitinase-3-like protein 1 (YKL-40) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…The inhibition of miR-335-3p resulted in the attenuation of chronic normobaric hypoxia-induced vascular remodeling and PAH in mice [91]. A significant increase in miR-30a-5p level in the plasma of PAH patients was recently reported [92]. Hypoxia exposure to HPAECs progressively downregulated miR-30a-5p and upregulated YKL-40 levels in a time-dependent manner.…”
Section: Pahmentioning
confidence: 83%
See 2 more Smart Citations
“…The inhibition of miR-335-3p resulted in the attenuation of chronic normobaric hypoxia-induced vascular remodeling and PAH in mice [91]. A significant increase in miR-30a-5p level in the plasma of PAH patients was recently reported [92]. Hypoxia exposure to HPAECs progressively downregulated miR-30a-5p and upregulated YKL-40 levels in a time-dependent manner.…”
Section: Pahmentioning
confidence: 83%
“…For example, miR-27a-3p attenuated pulmonary fibrosis, and in another report, miR-27a supported PAH [73,90]. Similarly, miR-30a interrupted the development of asthma, and on the other hand, miR-30a-5p promoted PAH [63,92]. miR-29a and miR-29c inhibited the pathogenesis of IPF, and miR-29b regulated inflammation in COPD [47,77,79,80].…”
Section: Comparative Role Of Mirnas In Lung Development and Diseasesmentioning
confidence: 93%
See 1 more Smart Citation
“…Total cellular protein extraction, protein concentration quantification and western blotting were performed as described in our previous report [20]. Briefly, proteins were transferred onto a polyvinylidene difluoride (PVDF) membrane after separation using sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE).…”
Section: Western Blottingmentioning
confidence: 99%
“…MicroRNAs (miRNAs or miRs) are a conserved class of small non-coding RNAs that can regulate gene expression at the post-transcriptional level (10). Recent studies have indicated that abundant miRNAs participate in the pathogenesis of PAH (11)(12)(13)(14). miR-27b has been shown to suppress endothelial cell proliferation and migration in Kawasaki disease (15).…”
Section: Introductionmentioning
confidence: 99%